2016
DOI: 10.14413/herj.2016.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between problem-solving and metacognition among university students entering university education

Abstract: Understanding and solution of science problems, advanced-level mastering of science knowledge and methods cannot take place without this ability. However, research has suggested that in recent years students starting their BSc in science do not possess the necessary level of this skill (Radnóti, 2010). Finding the reasons is a multi-faceted and complex task. This study describes an investigation whose purpose was to explore the interrelationships between problem-solving and metacognition. The investigation inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…However, the framework lacked the theory to adequately prepare the researcher for the results of the MAI and MAIT. The quantitative analysis found that the MAI and MAIT yielded similar conclusions to research carried out by Huszti et al (2016) and Siegesmund (2016), where participants tended to overestimate their metacognitive competence. The researcher overvalued what the MAIT and the MAI could accurately show because the teacher interviews revealed that none of the teachers had heard of the term metacognition and that they had not been given training in fostering metacognition in the classroom.…”
Section: Discussion and Recommendationssupporting
confidence: 63%
“…However, the framework lacked the theory to adequately prepare the researcher for the results of the MAI and MAIT. The quantitative analysis found that the MAI and MAIT yielded similar conclusions to research carried out by Huszti et al (2016) and Siegesmund (2016), where participants tended to overestimate their metacognitive competence. The researcher overvalued what the MAIT and the MAI could accurately show because the teacher interviews revealed that none of the teachers had heard of the term metacognition and that they had not been given training in fostering metacognition in the classroom.…”
Section: Discussion and Recommendationssupporting
confidence: 63%